A new localisation strategy with wireless sensor networks for tunnel space model. (3rd September 2019) - Huang, Ying; Luo, Yezhen; Lai, Honghui; Huang, Yiwang
Because the three-dimensional distance vector hop (DV-hop) localisation has some large error phenomena in the location of tunnel space model, an improved three-dimensional DV-hop fixed node location strategy is proposed based on the wireless sensor network for the relationship between the geometric model of tunnel space. This strategy analyses the deficiency of traditional three-dimensional DV-hop algorithm about counts hop and calculations distance on two WSN nodes, and it employs the relationship between beacon node and distance to modify the hop count of DV-hop, then using the differential method corrects distance error from the unknown node to the beacon node. According to the tunnel space model, the selection mechanism is introduced, and three optimal beacon nodes are selected to locate the unknown nodes and further improve the location accuracy. The traditional three-dimensional DV-hop calculation hops neglect the distance between nodes, the improved strategy is used to correct the distance between unknown nodes and beacon nodes. The experimental results show that the improved DV-hop localisation strategy has greatly improved the location accuracy; it can be widely used to solve the internet of things problem.